Efeito de diferentes óleos essenciais associados a biofilmes no controle da antracnose em qualidade de frutos do mamoeiro - Costa, Priscila Fonseca (Universidade Federal do Tocantins, 2018)
The papaya culture has great importance for national fruit growing due to its social and economic aspects, highlighting Brazil as one of the world's great fruit producers. Among the biological factors are the action of phytopathogens that cause great damage in field conditions and also in post-harvest. This will increase the demand for new natural-based products to help reduce these losses. Thus, the objective of this work was to evaluate the effect of different essential oils associated with biofilms in the papaya anthracnose control and in the post-harvest quality of fruits. A completely randomized design was used in all trials. Among the treatments, biofilms were used: gelatin, paraffin and sunflower oil which were incorporated into the essential oils of noni (Morinda citrifolia), rosemary pepper (Lippia sidoides) and their respective major compounds represented by octanoic acid and thymol. After treatments and after 24 h, the fruits were inoculated with disks of 6 mm diameter of C. gloeosporioides, and kept in a humid chamber for ten days at room temperature of 27 ± 3ºC. The essential oils presented significant efficiency in the inhibition of the conidial germination of Colletotrichum gloeosporioides. Disease control was assessed according to the Area Under the Disease Progression Curve (AACPD), where it w u h h m biofilm was paraffin with noni. It was verified that all the essential oils reduced the germination of conidia of C. gloeosporioides, due to the increase of the concentrations. Regarding mycelial growth, it was observed that the essential oils of noni and lippia had a greater inhibitory effect. In the evaluation of the loss of mass of the fruits were observed lower losses in the treatment using paraffin incorporated into the essential oil of rosemary pepper and paraffin incorporated into essential oil of noni. Regarding the influence of the treatment on the ripening period of the fruits, the sunflower oil + noni followed by sunflower oil + octanoic acid maintained the fruits without maturing for a longer time. Through the results it was possible to conclude that biofilms incorporated with essential oils are a viable option for the control of C. gloeosporioides in papaya and for maintenance of its post-harvest quality.